Toxicity Study Needs for Quantum Dots and Nanoparticles in PV Fabrication. Issue 1638 (17th February 2014) - Sadeghimakki, Bahareh; Sivoththaman, Siva
ABSTRACT: Quantum dots (QDs) and nanoparticles (NPs) with tunable optoelectronic properties are actively researched for photovoltaic (PV) fabrication and will enter mainstream manufacturing in the future. The toxicology, health and safety of these new materials are not fully explored yet. In this work, the toxicological potencies of nanomaterials in PV fabrication, study needs, and metrology requirements are presented. Practical processes involving QDs and NPs developed for PV fabrication are presented. Experimental evidence on the presence of airborne nanomaterials in the condensates collected from process environment underlines the need for in-depth toxicity studies before these technologies scale up to the PV manufacturing stage. Required technical capabilities for the metrology tools to accurately detect, identify, and quantify QDs and NPs in PV manufacturing requirements are also presented based on the potential range of nanomaterials to be used in PV technology. These studies are key to develop safe techniques and processing environments, and to establish safety guidelines for PV fabrication with nanomaterials.